Overview of traditional law in the use of Mayam as mahar in Aceh traditional marriage - Ryan Taufika; Tohap Pandapotan Simaremare; Vinda Chairunnisa; Tengku Syarifah Nadhira (Jurnal Civics: Media Kajian Kewarganegaraan)
Customary law is the law that regulates individuals or groups that regulate social order and the behavior of life in an indigenous community. This study aims to find out the customary rules regarding the understanding of dowry contained in the Aceh Pidie community and to find out the causes and consequences of increasing the value of the dowry in the mayam count. The method in this study used a descriptive analytical qualitative research method. To answer these questions, the analysis technique used by the researcher is descriptive analysis and uses data collection techniques using observation, documentation, and interviews. The results of the study show that the dowry in Acehnese traditional marriages in Pidie Regency has a negative influence. A prominent factor is where men and women are hampered because of the high demand for dowry which must be adjusted to the changing times regarding the price of gold which is calculated in mayam units. The factors causing the increase in dowry in Acehnese traditional marriages in Pidie Regency are seen in terms of lineage, beauty, and the level of education of prospective women.